2012
DOI: 10.1371/journal.pone.0043267
|View full text |Cite
|
Sign up to set email alerts
|

Man’s Underground Best Friend: Domestic Ferrets, Unlike the Wild Forms, Show Evidence of Dog-Like Social-Cognitive Skills

Abstract: Recent research has shown that dogs’ possess surprisingly sophisticated human-like social communication skills compared to wolves or chimpanzees. The effects of domestication on the emergence of socio-cognitive skills, however, are still highly debated. One way to investigate this is to compare socialized individuals from closely related domestic and wild species. In the present study we tested domestic ferrets (Mustela furo) and compared their performance to a group of wild Mustela hybrids and to domestic dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 33 publications
0
57
0
Order By: Relevance
“…Finally, dogs were presented with a Tolerance of prolonged eye contact trial (similar to that used by Hernádi et al, 2012) in order to assess whether, after having received intranasal oxytocin, dogs would show a higher tendency to keep eye contact with an unfamiliar human (for video protocol and photograph see Supplementary material S2). Dogs' readiness to establish and maintain eye contact with the E was recorded in room B.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Finally, dogs were presented with a Tolerance of prolonged eye contact trial (similar to that used by Hernádi et al, 2012) in order to assess whether, after having received intranasal oxytocin, dogs would show a higher tendency to keep eye contact with an unfamiliar human (for video protocol and photograph see Supplementary material S2). Dogs' readiness to establish and maintain eye contact with the E was recorded in room B.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Whether this is a general aspect of domestication or specific to highly cooperative dogs is not yet fully understood. However, recent research has shown that ferrets and pigs are able to perform some of the communicative skills normally associated with dogs (34,35), which indicates that this may be a general domestication trait.…”
Section: The Domesticated Phenotypementioning
confidence: 99%
“…Thus, domestication is sufficient to predict success on tasks such as following a human pointing gesture to locate hidden food. Other domesticated species including cats (Miklósi et al, 2005), goats (Kaminski et al, 2005), ferrets (Hernádi et al, 2012), horses (Maros et al, 2008), and pigs (Nawroth et al, 2013) have also demonstrated the ability to follow a human point. The Domestication hypothesis is further supported by studies demonstrating other possible genetic influences on point-following performance in dogs.…”
Section: Introductionmentioning
confidence: 99%